In vitro safety evaluation of sunscreen formulation from nanostructured lipid carriers using human cells and skin model - Chu, Chee Chin; Azizul Hasan, Zafarizal Aldrin; Tan, Chin Ping; Nyam, Kar Lin (Elsevier, 2022)
There is a risk of toxicological reactions due to systemic absorption and photo-instability of sunscreens. The study aimed to investigate the safety profile (cytotoxicity, phototoxicity, photostability, UV filter release profile, and skin irritation properties) of sunscreen (NLC-TRF sunscreen) produced from nanostructured lipid carriers (NLCs) and tocotrienol-rich fraction (TRF). The cytotoxicity and phototoxicity of the sunscreen were evaluated on normal human dermal fibroblast (NHDF) and skin irritation properties was tested on skin model. Besides, the photoprotection in pre- and post-UV irradiation were analysed to determine the photostability. Additionally, the release profile for UV filters (diethylamino hydroxybenzoyl hexyl benzoate (DHHB) and ethylhexyl triazone (EHT)) were evaluated. The NLC-TRF sunscreen demonstrated no cytotoxicity and skin irritation to cause cell death. It showed no phototoxic effect and high photostability up to 10 Minimal Erythema Dose (MED) to ensure high SPF value above 50 and broad-spectrum of UV absorption. The NLC-TRF sunscreen implies its safety for topical application with sustainable release profile for UV filter (cumulative release of 28% for DHHB and 40% for EHT after 8 h) due to the application of NLCs. The results suggest that the NLC-TRF sunscreen is an advanced formulation with improved stability and is safe for topical delivery.